Florida and the Mariel Boatlift of 1980 : the First Twenty Days. - Hawk, Kate Dupes, 1941- (University of Alabama Press, 2014)
The 1980 Mariel Boatlift was a profound episode in twentieth-century American history, impacting not just Florida, but the entire country. During the first twenty days of the boatlift, with little support from the federal government, the state of Florida coordinated and responded to the sudden arrival in Key West of more than thirty thousand Cuban refugees, the first wave of immigrants who became known as " Marielitos." Kathleen Dupes Hawk, Ron Villella, Adolfo Leyva de Varona, and Kristen Cifers combine the insights of expert observers with